The Influence of Current Ratio, Quick Ratio and Net Profit Margin on Return on Investment at PT. Telekomunikasi Indonesia (Tbk) - Neneng Susanti (Universitas Negeri Makassar, 2020)
Financial management is very influential on the continuity of activities and the existence of a company and also affects every individual in the company. This study aims to determine the effect of the current ratio, quick ratio and net profit margin on return on investment at PT. Telekomunikasi Indonesia (Tbk) 2014-2018. The method used is explanatory research with a sample of 5 years of financial statements that have been made panel data. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the current ratio does not significantly influence the return on investment of 50.7%, the hypothesis test obtained a significance of 0.177> 0.05. The quick ratio does not significantly influence the return on investment of 51.4%, the hypothesis test obtained significance of 0.173> 0.05. Net profit margin has a significant effect on the return on investment of 86.6%, hypothesis testing obtained significance of 0.022 <0.05. The current ratio, quick ratio, and net profit margin simultaneously have a significant effect on the return on investment of 99.2%, hypothesis testing is obtained 19,836> 9,280..